A Study On Variations In Sewerage Construction Projects - Kassim, Mohd. Azraai (Penerbit UTM Press, 2002)
Variations in construction have long been a debatable issue among the different participants involved in construction projects. However, only a few formal studies have been carried out to analyse its causes and effects. This study is focused on the frequency and severity of various factors causing variations in sewerage networks construction projects. It is important for a company not only to know the variation costs, but also to identify the most likely areas on which to focus in order to reduce these costs for the future projects. All the necessary data and information are obtained from archival files of thirteen projects and verified through interviews. These data are categorised to analyse the frequency and severity of factors. Tables and charts are presented to show the research findings. From the analysis, differing site conditions appear to be the major factors contributing to variations. They average 49.3% of the total number of variations, 56.2% of the total variation costs and 3.8% of the total project costs. Two project characteristics i.e. contract award value and the contractor’s registration grade with the Construction Industry Development Board (which represents the contractor’s specialisation, financial and other resources standing) [1] show certain causal relationships with variations.